A Critical Analysis of Collaborative Approaches - Rukmana, Fitriana Arum Dita (PCD Journal, 2025)
This article analyses the critical collaboration between the civil community and the government. Forum Komunitas Sungai Sleman (FKSS), in association with the Environmental Agency of Sleman regency, endeavors to resolve the environmental issue of river water pollution that occurs around Sleman regency. This collaboration between was analysed by looking at the critical engagement of FKSS and employing social movement theory. This theory is relevant because it explains how collective community actions can influence policy and governance processes. River water pollution is a persistent environmental issue in many developing regions, including Indonesia, where local community involvement in governance is still limited. This article employs a case study research method and follows qualitative research principles. Data for this study were collected through observation, interviews, and a review with relevant literature. The interviews were conducted with six participants. The research concludes that FKSS functions not as a governmental instrument for issue resolution but as a cooperative partner in governance. FKSS also granted specific authority to engage in the decision-making process, collaborate as a governmental partner, and critically evaluate governmental policies. The findings provide insight for policymakers seeking to strengthen community-based environmental governance.